Elevated Anti-Müllerian Hormone Is an Independent Risk Factor for Preterm Birth Among Patients With Overweight Polycystic Ovary Syndrome - Du, Mingze; Zhang, Junwei; Yu, Xiaona; Guan, Yichun (Frontiers in Endocrinology, 2021)
Objective: To explore whether elevated anti-Müllerian hormone (AMH) levels affect the rate of preterm birth (PTB) among PCOS patients with different BMIs. Methods: In this retrospective cohort study, patients with PCOS who had undergone IVF/ICSI from January 2017 to December 2019 were included for potential evaluation. A total of 2368 singleton live births from PCOS patients were included. According to the BMI, all the PCOS patients were divided into two groups: BMI<24 kg/m2 and BMI≥24 kg/m2. In total, 1339 PCOS patients with a BMI<24 kg/m2 were grouped according to their serum AMH levels: ① <2.71 ng/ml (n=333), ② 2.71-4.08 ng/ml (n=330), ③ 4.09-6.45 ng/ml (n=351), and ④ >6.45 ng/ml (n=325). Additionally, 1029 cycles of patients with a BMI≥24 kg/m2 were grouped according to the serum AMH level: ① <2.71 ng/ml (n=255), ② 2.71-4.08 ng/ml (n=267), ③ 4.09-6.45 ng/ml (n=239), and ④ >6.45 ng/ml (n=268), with <2.71 ng/ml being considered the reference group. The grouping was based mainly on the interquartile range of serum AMH levels. The primary outcome of the study was PTB. The secondary outcomes were low birth weight (LBW), small for gestational age (SGA), macrosomia and large for gestational age (LGA). Results: Regarding PCOS patients with a BMI<24 kg/m2, compared with the PTB rate of the AMH <2.71 ng/ml group, the PTB rates of the different groups were not significantly different (AMH 2.71-4.08, AOR (95% CI)=1.01 (0.52-2.00), P=0.99; AMH 4.09-6.45, AOR (95% CI)=0.93 (0.45-1.91), P=0.85; AMH>6.45, AOR (95% CI)=0.78 (0.35-1.73), P=0.54). Regarding PCOS patients with a BMI ≥24 kg/m2, compared with the PTB rate of the AMH <2.71 ng/ml group, the PTB rate of the AMH>6.45 ng/ml group was significantly higher (OR=2.47; 95% CI=1.34-4.55). After multiple logistic regression analysis, the risk of PTB in the AMH>6.45 ng/ml group was 2.1 times that in the AMH<2.71 ng/ml group (AOR=2.1, 95% CI=1.01-4.37, P=0.04). However, no statistically significant difference was found in the rate of SGA, LBW, macrosomia or LGA among patients in the different serum AMH groups. Conclusion: For PCOS patients, a BMI≥24 kg/m2 plus serum AMH>6.45 ng/ml (75th percentile) is an independent risk factor for PTB.